Perkembangan Asas Desantralisasi Pada Masa Sebelum Reformasi dan Sesudah Reformasi - Acnes M sitorus; Elmi Rutmita; Marintan F Silalahi (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
The term autonomy etymologically comes from the Latin "autos" which means to be alone and "nomos" which means to regulate, so that autonomy can be interpreted as self-regulation, regulation or self-government. Regional autonomy is the authority given by the state to autonomous regions to regulate and manage their households. itself in accordance with applicable laws and regulations. Autonomy aims to improve community welfare. However, the effectiveness of its implementation remains a bad thing. Overall, regional autonomy in Indonesia is still in the development stage and there are still many challenges that need to be overcome, although there have been several implementations of autonomy that have been carried out in accordance with the rules of regional autonomy.